Hell in the Holy Land : World War I in the Middle East - Woodward, David R., 1939- (Lexington, Ky. : University Press of Kentucky, 2006)
Woodward uses graphic eyewitness accounts from the diaries, letters, and memoirs of British soldiers who fought in that war to describe in detail the genuine experience of the fighting and dying in Egypt and Palestine.
List of maps -- List of abbreviations -- Preface -- Acknowledgments -- Eastward bound -- Land of the pharaohs -- Clearing the Sinai -- Johnny Turk triumphant -- Bloody bulls loose -- Breakout -- Relentless pursuit -- Sacred soil -- Changing priorities -- Jordan valley -- Megiddo -- Conclusion -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 234-240) and index.
Print version record.
English.
JSTOR
Keywords: World War, 1914-1918 -- Campaigns -- Middle East; World War, 1914-1918 -- Personal narratives, British; Soldiers -- Great Britain -- Correspondence; HISTORY -- Military -- World War I; HISTORY -- Middle East -- General; Military campaigns; Soldiers; Great Britain; Middle East; 1914 - 1918; Personal narratives -- British; Personal correspondence